Penerapan Metode PIECES pada Analisis Sistem Informasi Manajemen Apotek - Intan Oktaviani; Sri Sumarlinda (Universitas Duta Bangsa Surakarta, 2021)
Pharmacy is one of the first public health services. The Management Information Sistem at a pharmacy that is still using a conventional sistem is only recorded on paper for all data management processes for drug ordering, drug purchases, drug purchase returns, drug sales, drug sales returns and taking stock. So that the information generated is less accurate. The data needed is sometimes lost or damaged when it is stored because it is still written on paper. The conventional sistem of pharmacies does the writing of sales reports on sales books that are done after making a sales transaction, sometimes it takes time because of the large amount of drug data that must be written. This results in the sales transaction service process taking a long time and complaints from consumers due to the long service process. In this research, the sistem will be designed using the waterfall sistem development method with the Data Flow Diagram (DFD) modeling flow. Then a sistem analysis will be carried out using the framework of Performance, Information, Economics, Control, Efficiency, Service (PIECES). The sistem analysis resulted from this research is a sistem that can be used to manage drug ordering data, drug purchase data, drug purchase return data, drug sales data, drug sales return data and drug taking stock data so that pharmacies can improve services to consumers more effectively and efficient. The application of the PIECES method in sistem design results in a comparison of the sistem process between the running sistem and the sistem being developed.